ATRAZINE REDUCES THE CRITICAL PERIOD OF WEED INTERFERENCE ON NARROW ROW CORN - Padilha, M. (2016)
The objective was to determine whether a change occurs in the critical period of weed interference prevention in narrow row corn with the use of atrazine and whether there is influence of the herbicide on crop yield components. The treatments consisted of periods without or with an initial weed control (0, 21, 35, 49, 63, 77, and 91 days after emergence), with or without application of atrazine in spikely post-emergence. The experiment was carried out in a 2 x 7 randomized blocks design (with and without weed control and seven periods with three replications). The use or not of atrazine was arranged in a split plot design. The most important weed species were Senecio brasiliensis, Urochloa plantaginea, Conyza bonariensis, Sida rhombifolia, and Solanum spp. Corn yield reduced by 15% and 18% with and without application of atrazine, respectively. The number of grains per spike and corn yield were negatively influenced by coexistence with weeds, while the number of rows per spike, the diameter and length of spike were not affected. Corn yield components were not affected by the use of atrazine. The critical period of weed interference prevention was 35 days without atrazine and 23 days with application of atrazine. There is a reduction of the critical period of weed interference prevention on narrow row corn by using atrazine, with no influence of the herbicide on crop yield.